Functional Outcome of Conservatively Managed Ulnar Styloid Fracture on Wrist Function - Yasin, Azhar; Khan, Ahmad Mushtaq; Muhammad Nadeem; Muhammad Shoaib; Alam, Syed Asad Ullah (Indus Journal of Bioscience Research, 2025)
Objective: This study aims to evaluate the functional outcome of conservatively managed ulnar styloid fractures and their effect on wrist function. Ulnar styloid fractures are commonly associated with distal radius injuries and may influence distal radioulnar joint (DRUJ) stability, potentially affecting overall wrist mechanics. Methods: A retrospective observational study was conducted including 80 patients with ulnar styloid fractures managed conservatively using immobilization followed by rehabilitation at Department of Orthopedic Surgery, Combined Military Hospital, Rawalpindi. Patients were assessed at 6 weeks and 12 weeks follow-up. Functional outcomes were evaluated using the Patient-Rated Wrist Evaluation (PRWE) score, range of motion (ROM), and grip strength. Additional clinical parameters such as pain, joint stability, and complications were also recorded. Results: The majority of patients demonstrated satisfactory functional recovery with significant improvement over time. The mean PRWE score improved from 49.8 ± 10.2 at 6 months to 41.2 ± 9.5 at 1 year (p < 0.05), indicating reduced pain and disability. Wrist ROM, particularly flexion and extension, showed statistically significant improvement (p < 0.05), while radial and ulnar deviation improved but were not statistically significant. Grip strength increased gradually but did not reach full recovery compared to the contralateral side. A small proportion of patients reported persistent mild pain and occasional instability. Conclusion: Conservatively managed ulnar styloid fractures generally result in favorable functional outcomes with significant improvement in pain and wrist mobility over time. However, some patients may experience residual symptoms, particularly reduced grip strength and mild discomfort. These findings highlight the importance of proper rehabilitation and follow-up to optimize wrist function after conservative treatment.